Relationship between the perceived organizational climate and teachers' job commitment / 'Afifah Shamsul Anuar - Shamsul Anuar, 'Afifah (2014)
Teachers want a work environment in which interpersonal relations are trusting and healthy (Smith, Hoy, & Sweetland, 2001). The two concepts are complementary to each other. A healthy organizational climate facilitates the development of faculty trust; in turn, faculty trust promotes a healthy organization. This study examined the perceived organizational climate among teachers and their level of job commitment. In addition, this study also aimed to investigate the relationship between school climate and teacher commitment. The study focused on secondary schools in the suburban area located in Selangor. Thirty school teachers from two secondary schools took part in this study. The findings revealed that the crucial interactions that make up organizational school climate are those of teacher to teacher and teacher to principal. It was also found that there was a significant relationship between the school organizational climate and teachers' job commitment. A principal's influence and collegiality among the teachers contribute to teacher commitment.